2015
DOI: 10.1038/mt.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of antigen-presenting cells in the brain by AAV9 warrants caution in preclinical studies

Abstract: letters to the editor 612 www.moleculartherapy.org vol. 23 no. 4 april 2015 full immunotoxic effect is not visible for at least a month. Thus, the apparent discrepancy between our published data and the present study can be explained entirely in terms of the acute nature of the experiment performed by Hinderer et al. We agree that 2 weeks would not reveal significant signs of a classic immune response against a foreign antigen, and we caution other investigators that safety studies designed to reveal possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The marked reductions in LED in cohorts 2 and 3 did not occur in cohort 1, nor in the two earlier AADC gene therapy trials, likely because of lower volumetric coverage of the putamen by the vector. Together with the 18 F‐dopa PET data, and the findings from the intravenous levodopa substudy, these LED reductions suggest an increased ability to convert levodopa to dopamine, and a reduced need for dopaminergic medications that is consistent with the expected pharmacological effect of AADC gene therapy …”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The marked reductions in LED in cohorts 2 and 3 did not occur in cohort 1, nor in the two earlier AADC gene therapy trials, likely because of lower volumetric coverage of the putamen by the vector. Together with the 18 F‐dopa PET data, and the findings from the intravenous levodopa substudy, these LED reductions suggest an increased ability to convert levodopa to dopamine, and a reduced need for dopaminergic medications that is consistent with the expected pharmacological effect of AADC gene therapy …”
Section: Discussionmentioning
confidence: 66%
“…Dyskinesia responded to reductions in antiparkinsonian medications, and diary data showed a trend toward improvements in troublesome and nontroublesome dyskinesia (Fig 5). 11,21 We found that the response at 12 months measured by UPDRS-III in the on-medication state improved by a clinically meaningful 22 -9.6 and -6.8 points in cohorts 2 and 3, respectively. Volumes of administration up to 900 μl per putamen were well tolerated and represent a 9-fold increase in volume compared to earlier AADC gene therapy trials.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Tissue analysis of the injection sites revealed that AAV2-HBKO vector carrying a foreign protein (EGFP) triggered an immune reaction after being infused into the parenchyma, a finding consistently observed with expression of EGFP into antigen-presenting cells in the brain. [26][27][28] H&E staining revealed perivascular cuffing and cellular infiltration in the thalamus, and to a lesser extent in the secondary transduction areas. Astrocytic activation and microglial hyperactivity were also evident from glial fibrillary acidic protein (GFAP) and Iba1 staining in the thalamus, indicating a clear immune reaction ( Figure S1).…”
Section: Thalamic Aav2-hbko Infusion Results In Bidirectional Axonal mentioning
confidence: 93%
“…AAV9 evinces a broad tropism in neural tissues, 17 19 transducing neurons and astrocytes as well as perhaps other cell types. The ability of AAV9 to transduce antigen-presenting cells (APC) in the brain has risen concerns with respect to expression of foreign (non-self) proteins 7 , 8 , 20 in APC and the consequent engagement of neurotoxic adaptive immune responses. This, of course, is not likely to be a problem when self-proteins are expressed, but in the present study we observed, as previously, activation of Iba1 and upregulation of MHC-II on astrocytes and microglia ( Fig.…”
Section: Discussionmentioning
confidence: 99%